UPAYA PERENCANAAN PEMBANGUNAN DESA DALAM BIDANG INFRASTRUKTUR UNTUK MEWUJUDKAN KESEJAHTERAAN MASYARAKAT - Alpianus Malo; Firman Firdausi (JISIP : Jurnal Ilmu Sosial dan Ilmu Politik, 2019)
Abstracts: The implementation of regional autonomy that based on structured development planning byon time according to the Republic of Indonesia Law Number 25 of 2014 concerning NationalDevelopment Planning. Therefore this research is: To find out the efforts of village infrastructuredevelopment planning to actualize the public welfare. This researcher uses qualitative approaches, Datacollection through observation, interview, and documentation techniques. The sampling technique thatuses is purposive sampling. The validity of the data using triangulation techniques. Analysis by reduction,presentation and conclusion. The result of this planning effort of village infrastructure development toactualize public welfare research was successful and implemented well because of the efficiency andrationality, the institutions role and professionalism has been going well and can be seen from the villagegovernment task and responsibility, and change or expand the choices to reach the higher level of welfareand the results of consensus between the government and the community are received and that so theinfrastructure development program in 2017 is going well. Supporting factors include: Freedom of thepublic participation, community support for government policies, distribution of financial support. Whilethe inhibiting factors include: lack of supervision team, lack of builders, weather conditions.Keywords: Development Planning, Infrastructure, Public WelfareAbstrak: Pelaksanaan otonomi daerah yang di dasarkan pada perencanaan pembangunan yang terstrukturberdasarkan tingkatan waktunya menurut Undang-Undang Republik Indonesia Nomor 25 Tahun 2014Tentang Perencanaan Pembangunan Nasional. Dengan demikian yang menjadi penelitian yaitu: Untukmengetahui upaya perencanaan pembangunan desa dalam bidang infrastruktur untuk mewujudkankesejahteraan masyarakat. Penelitian ini menggunakan jenis pendekatan kualitatif. Pengumpulan datamelalui teknik observasi, wawancara, dan dokumentasi. Teknik sampling menggunakan purposivesampling. Keabsahan data menggunakan teknik triangulasi. Analisis dengan reduksi, penyajian danpenarikan kesimpulan. Hal ini hasil dari pada penelitian ini berhasil dan terlaksana karena efisien danrasionalitas, peran kelembagaan dan profesionalitas sudah berjalan dengan baik apa yang menjadi tugasdan tanggungjawab pemerintah desa, sehingga program pembangunan infrastruktur di Tahun 2017berjalan dengan baik. Faktor-faktor pendukungnya meliputi: Kebebasan terhadap masyarakat, dukunganmasyarakat, dukungan finansial. Sedangkan faktor-faktor penghambat nya meliputi: kurangnya timpengawasan, kurangnya tukang bangunan, kondisi cuaca.Kata Kunci : Perencanaan Pembangunan, Infrastruktur, Kesejahteraan Masyarakat